2021
DOI: 10.1016/j.celrep.2021.108896
|View full text |Cite
|
Sign up to set email alerts
|

EGF-mediated suppression of cell extrusion during mucosal damage attenuates opportunistic fungal invasion

Abstract: EGF-mediated suppression of cell extrusion during mucosal damage attenuates opportunistic fungal invasionGraphical abstract Highlights d Inducible epithelial cell loss allows modeling of fungal infection in zebrafish larvae d Extrusion of numerous cells exposes laminin and increases fungal adhesion and invasion d Cell extrusion stimulates epigen, mmp13a, and il1b expression and neutrophil recruitment d rhEPGN suppresses extrusion to provide protective effects against fungal invasion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 85 publications
0
24
0
Order By: Relevance
“… Note: Extrusion and the extent of associated tissue damage can be assessed by using the Et(Gal4-VP16) zc1044a , Tg(UAS-1b:nsfB-mCherry) c264 line in conjunction with other transgenic lines such as, Tg(UAS-1b:Lifeact-EGFP) utm1 ; Tg( k rt4:GFP); and Tg(-8.0cldnb:lynEGFP) zf106 that allow for independent visualization of both the surface epithelial cells and cell-cell contacts. For additional details about quantification of the resulting epithelial tissue damage, please see ( Wurster et al., 2021 ). …”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“… Note: Extrusion and the extent of associated tissue damage can be assessed by using the Et(Gal4-VP16) zc1044a , Tg(UAS-1b:nsfB-mCherry) c264 line in conjunction with other transgenic lines such as, Tg(UAS-1b:Lifeact-EGFP) utm1 ; Tg( k rt4:GFP); and Tg(-8.0cldnb:lynEGFP) zf106 that allow for independent visualization of both the surface epithelial cells and cell-cell contacts. For additional details about quantification of the resulting epithelial tissue damage, please see ( Wurster et al., 2021 ). …”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“… Note: Considering a remainder of 100 μL E3 medium in the wells after the last wash step, addition of 1 mL of fresh E3 medium and the 100-μL volume of the spore inoculum itself, this inoculum results in our recommended standard spore concentration of 5×10 6 /mL. However, we have previously shown that the infection severity can be easily adjusted by using up to 10-fold lower or higher spore inoculums (as seen in Figure 1L in ( Wurster et al., 2021 ). CRITICAL: All experiments should include control groups of uninfected larvae with epithelial homeostasis and induced epithelial cell loss, respectively, as a sentinel for non-infection-attributable baseline mortality.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 3 more Smart Citations